2001
DOI: 10.1351/pac200173121819
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical technology for environmental treatment and clean energy conversion

Abstract: Abstract:The applications of electrochemical technology in environmental treatment, materials recycling, and clean synthesis are briefly reviewed. The diversity of these applications is shown by the number of industrial sectors involved. The scale of operation ranges from microelectrodes to large industrial cell rooms. The features of electrochemical processes are summarized.Available and developing electrode designs are considered and illustrated by examples including the regeneration of chromic acid electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(97 citation statements)
references
References 14 publications
3
89
0
5
Order By: Relevance
“…Over the past 30 years, the design of electrochemical cells and reactors has been influenced by the availability and ability to shape different types of material to a particular cell or reactor [2,83]. RVC has contributed, continuing to be used as a model electrode in the design and construction of new electrochemical cell designs, both in fundamental and applied electrochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, the design of electrochemical cells and reactors has been influenced by the availability and ability to shape different types of material to a particular cell or reactor [2,83]. RVC has contributed, continuing to be used as a model electrode in the design and construction of new electrochemical cell designs, both in fundamental and applied electrochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Also, each term in the models are also examined for signifi cance 19 . A p-value smaller than 0.05 implies that 20 . In addition, the linear term for B and D is also signifi cant but with a smaller effect of A and C on the response Y 4 , due to its smaller F-value.…”
Section: Resultsmentioning
confidence: 99%
“…Studies involving these threedimensional electrodes can be found extensively in the literature. The use of three-dimensional electrodes increases the reactor design complexities due to their non-uniform current and potential distribution [5,6].…”
Section: Reactor Design and Operation Modesmentioning
confidence: 99%